A comparative study of ferric carboxymaltose and iron sucrose as a parenteral iron treatment in iron deficiency anemia during pregnancy in a tertiary care hospital - Sandip Kumar Ghosh; Raston Mondal; Sutapa Mandal; Arindam De (Asian Journal of Medical Sciences, 2024)
Background: Anemia from the Greek word (anhaima) meaning “without blood” is the deficiency of red blood cell and/or hemoglobin which result in reduced oxygen-carrying capacity of blood causing tissue hypoxia. Aims and Objectives: To study the efficacy and safety of intravenous ferric carboxymaltose (FCM) versus iron sucrose in the management of iron deficiency anemia in pregnancy. Materials and Methods: A prospective, single-center, comparative interventional randomized study was carried among 180 antenatal mother admitted to antenatal ward in the Department of Obstetrics and Gynaecology of Burdwan Medical College and Hospital, from July 1st, 2020, to December 30th, 2021. Results: A total of 180 patients, 90 patients in each FCM and iron sucrose group, were included in the study. There was significant (P=0.001) mean change in hemoglobin (Hb) level in both the groups from pre-treatment to 3 and 6-week post-treatment. There was also a significant (P=0.001) mean change in ferritin level in both the groups from pre-treatment to 3 and 6-week post-treatment. The mean change in Hb level and ferritin level was higher among patients of FCM compared to iron sucrose. The adverse reactions were lower among patients of FCM than iron sucrose. Conclusions: This study found that FCM is safer than iron sucrose. Treatment with FCM resulted in rapid replenishment of iron stores in pregnant women with significantly high rise of Hb and ferritin levels over a 6-week period with lesser adverse effects.